The Fate of Altertoxin II During Tomato Processing Steps at a Laboratory Scale - Puntscher, Hannes; Marko, Doris; Warth, Benedikt (Frontiers in Nutrition, 2019)
Among various agricultural crops, tomatoes are particularly prone to Alternaria infections, which are frequently resulting in economic losses and mycotoxin contamination. To investigate potential health concerns implied for consumers, we simulated the storage and food processing steps of intact and blended tomatoes after addition of the highly genotoxic secondary metabolite altertoxin II. We observed a significant decrease in altertoxin II concentrations in samples stored at room temperature and particularly those undergoing thermal treatment by employing a validated LC MS/MS method. When kept at room temperature, 87-90 % of ATX II was recovered after 1.5 h in raw tomato purees and purees heated before ATX-II addition, and 47-49 % were recovered after 24 h. In intact tomato fruits the recovery was 23 % after 1.5 h and <1 % after 24 h. In heated purees (100 °C for 30 min after ATX-II addition), also only minor concentrations accounting for 2 4 % were determined. Moreover, the reduction of the compound’s epoxide group to the alcohol, i.e. the formation of altertoxin I was demonstrated in intact tomato fruits (7-12 %), suggesting enzymatic biotransformation of the xenobiotic by the plant’s metabolism.